Application of blockchain technology for beverage safety in intelligent ready-made beverage machines - XU, Bifeng; CHEN, Chaoxue; LI, Chenghai; SHAO, Lifeng; YU, Jiao (Food Science and Technology, 2023)
In recent years, beverage machines are popular and have a wide market, but the current beverage machines have insecurity factors such as low efficiency of source control, the possibility of data being tampered with, lack of intelligent warning and forced termination, and are not suitable for intelligent vending of various foods and beverages, so the market is in urgent need of a beverage machine with a secure traceability system. This paper proposes a hash consistency scheme of blockchain technology to address such problems, which can well solve the consistency problem, effectively prevent information from being tampered with, make source information transparent and have strong security, and design experiments for the anti-tampering function of blockchain, and the experimental results show that the application of blockchain technology in beverage machines can greatly improve the safety of beverages.